A ação herdada pelo Messias de YHWH em Salmo 2,9 - Lima, Édilon Rosales de (2021)
This research deals with the different translations of Ps 2,9 in the Hebrew text and in the Greek text, trying to understand what the messiah of YHWH receives from his father as an inheritance. Using the exegetical technique, the study is conducted to understand the formation of the poem of Psalm 2 in its Hebrew context, as well as its consolidation in the Greek canon. In such a way, it will be possible to come up with propositions that can collaborate on why the LXX reads the MT differently, and one should also understand the inheritance of the messiah in Ps 2.9.